Evaluation of heavy metals in superficial sediments of Pirro river - Herrera-Núñez, Jacqueline (2013)
Anthropogenic activities are important sources of heavy metals, which are dangerous for the aquatic biota and the human being and a factor of environmental and water quality deterioration. The sediments, one of the main reservoirs of these elements, act as secondary resources of contamination of the rivers; this is why it is important to evaluate the concentration of metals, as a tool that allows to track the origin of the contaminants in the environment and to predict their impact on the aquatic ecosystems. In the present study, the concentration of Cd, Ag, Se, Sn, Ni, Cr, Cu, B, Zn, Hg, Ba, Pb, Mn, As and Al was determined in the superficial sediments of the medium sector of Pirro River (Heredia, Costa Rica) by using atomic absorption spectrophotometry. The concentrations of these elements were very high for the majority of the elements analyzed in all sampling points. Its distribution was not homogeneous, nor it presented a define geographical pattern, since high levels were found along the entire riverbed.